(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the proper nouns of the German language, in which the theoretical basis of the classification of proper nouns in German linguistics, and their grammatical features that distinguish them from common nouns are subjected to scientific analysis.